SHADER METAMODEL AS A COMPONENT OF AN INTERACTIVE APPLICATION ARCHITECTURE - V. Kazantsava; Y. Baranouski; Y. Landarski (Informatika)
This article introduces the rendering metamodel as an architecture basis for complicated graphi-cal applications. The model separates abstract logical and algorithmic approaches used in modern computer graphics theory from problems of computational resource management. It also yields wide possibilities for program code complexity management.